POLA PENDIDIKAN KARAKTER MELALUI PENERAPAN 9 PILAR DI SEKOLAH KARAKTER INDONESIA HERITAGE FOUNDATION - Nufus, Fika Pijaki; R, M. Dahlan; Hakiem, M. Hilman (EDUTECH CONSULTANT, 2019)
The problem in this study is to find out how the pattern of character education through the application of 9 pillars in the Indonesian Heritage Foundation character school and its opportunities and challenges. The purpose of this study was to determine the pattern of application of character education in the elementary school of the Indonesian character Heritage foundation. The method used in this study is a qualitative field method with data analysis using interview, observation, and documentation methods. Conclusion The application of 9 character pillars is flowed every morning for 20 to 25 minutes before learning begins.